In Vitro Genetic Recombination of Bacteriophage λ - Syvanen, Michael (1974)
DNA of bacteriophage λ recombines in a cell-free extract prepared from an induced Escherichia coli lysogen of bacteriophage λ. The assay for recombination in vitro takes advantage of the ability of such an extract to package λ DNA and to assemble complete phage particles. For example, when λ DNA that has been extracted from phage with the immunity of 434 is added to an extract, infectious λ imm 434 particles are produced. The precursor DNA molecule in this packaging reaction is a multichromosomal polymer; circular monomers, for example, are not packaged. Nevertheless, when 434 circular DNA monomers are added to an extract, some phage that contain the imm 434 marker are produced. In this case, the circular DNA had recombined with λ DNA in the extract and thereby had become part of a polymeric structure, which by the normal packaging process could give rise to infectious particles with the imm 434 marker. Genetic recombination is demonstrated when imm 434 circular monomer DNA carries amber mutations in genes A and B; then most of the 434 plaque formers produced in vitro are A(+)B(+), the genotype of the endogenous λ DNA. Genetic crossing-over occurs through a region that contains the prophage attachment site, suggesting that recombination is carried out by the λ Int functions. The 434 recombinant plaque formers are particles physically identical to wild-type 434 particles, as judged by their buoyant density in a CsCl equilibrium gradient.